2004
DOI: 10.7863/jum.2004.23.7.907
|View full text |Cite
|
Sign up to set email alerts
|

Second‐Trimester Sonographic Comparison of the Lower Uterine Segment in Pregnant Women With and Without a Previous Cesarean Delivery

Abstract: The lower uterine segment during a second-trimester sonographic examination is significantly thinner in women with a previous cesarean delivery. Identification of the scar niche is possible in most of these women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…They hypothesized that uterine dehiscence of scarred uterus may be related to altered biochemical behaviour of the scarring process. 6 No neonatal death was seen in any of the groups. No statistically significant difference was seen in neonatal outcome in both groups.…”
Section: Resultsmentioning
confidence: 97%
“…They hypothesized that uterine dehiscence of scarred uterus may be related to altered biochemical behaviour of the scarring process. 6 No neonatal death was seen in any of the groups. No statistically significant difference was seen in neonatal outcome in both groups.…”
Section: Resultsmentioning
confidence: 97%
“…At present, the mechanisms by which prior CD affect the length of pregnancy are unknown. In a literature review, women who had undergone a previous CD were reported to have a significantly thinner anterior myometrium at the lower uterine segment after delivery and in subsequent pregnancy compared with women who had delivered vaginally . Although there is no direct evidence supporting early‐onset uterine contractions in women who have had a previous CD, a mathematical model for simulating uterine contractions indicate that thinning of the myometrium has a direct impact on uterine wall stress, which could, in turn, trigger myometrial activation leading to the synchronization and coordination of uterine contractions .…”
Section: Discussionmentioning
confidence: 99%
“…In one report, the mean thickness of the anterior lower segment and the mid-anterior, fundal, and posterior wall was 7.4, 9.1, 9.8, and 10.1 mm, respectively. 21 Sambaziotis et al 22 reported that the lower uterine segment during a second-trimester sonographic examination was significantly thinner in women with a previous cesarean delivery. Their results may suggest poor vascular supply at the anterior lower segment in women with previous cesarean delivery, resulting in active migration of the placenta.…”
Section: Discussionmentioning
confidence: 99%